The Model of Cultural Based Tourism Management in Urban Community : A Case Study of Thai-Vietnamese Community in Mukdahan Province, Thailand - Vasayangkura, Chanvit; Kunphoommarl, Montri (Mekong-Salween Civilization Studies Journal, 2016)
This study was a qualitative research conducting the community-based participatory action research. The objectives of the research were to study key success factors of Cultural Based Tourism Management and to synthesize the model of Cultural Based Tourism Management which is appropriate for urban communities. By applying the process and the model of successful Cultural Based Tourism Management of PuThaiBaanpu Community, a rural village, TambonBaanpao, Nongsung District, Mukdahan Province, possessing the cultural identity, which is a key factor for effective promoting the community tourism in the concept of 5A’s, was drawn and applied in the Cultural Based Tourism Management of Ruampattana Srimongkol Community: Thai-Vietnamese urban community in the municipality of Mukdahan Province. The qualitative research techniques, including focus group discussion, in-depth interview, participant, non-participant observation and community meeting were used to collect the data. The results were revealed that the successful Cultural Based Tourism Management of PuThaiBaanpu Community, a rural village based on the concept of 5A’s, can be applied to the Cultural Based Tourism Management of Ruampattana Srimongkol Community located in the municipality of Mukdahan Province with regard to the cultural capital which is the community identity.